Key policy challenges and opportunities to improve care for people with mental health and substance use disorders : proceedings of a workshop - Graig, Laurene A.; Friedman, Kaitlyn; Alper, Joe; National Academies of Sciences, Engineering, and Medicine (U.S.). Forum on Mental Health and Substance Use Disorders; Key Policy Challenges and Opportunities to Improve Care for People with Mental Health and Substance Use Disorders (Workshop) (2019 : Washington, D.C.) (Washington, DC : The National Academies Press, 2020)
Behavioral health and substance use disorders affect approximately 20 percent of the U.S. population. Of those with a substance use disorder, approximately 60 percent also have a mental health disorder. Together, these disorders account for a substantial burden of disability, have been associated with an increased risk of morbidity and mortality from other chronic illnesses, and can be risk factors for incarceration, homelessness, and death by suicide. In addition, they can compromise a person's ability to seek out and afford health care and adhere to treatment recommendations. To explore data, policies, practices, and systems that affect the diagnosis and provision of care for mental health and substance use disorders, the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine created the Forum on Mental Health and Substance Use Disorders. The forum activities are expected to advance the discussion and generate potential ideas on ways to address many of the most persistent problems in delivering mental health and substance use services. The inaugural workshop, held October 15-16, 2019, in Washington, DC, explored the key policy challenges that impede efforts to improve care for those individuals with mental health and substance use disorders. This publication summarizes the presentations and discussion of the workshop.
Intro -- FrontMatter -- Reviewers -- Acknowledgments -- Contents -- Boxes, Figures, and Tables -- Acronyms and Abbreviations -- Proceedings of a Workshop -- Appendix A: Workshop Agenda -- Appendix B: Statement of Task
Includes bibliographical references.
This activity was supported by Contract No. 200-2011-38807 (Task Order No. 75D30118F00073) with the Centers for Disease Control and Prevention, Purchase Order No. 75FCMC19PO036 with the Centers for Medicare & Medicaid Services, Contract No. HHSH250201500001I with the Health Resources and Services Administration, Contract No. HHSN263201800029I (Task Order No. HHSN26300025) with the National Institutes of Health, Contract No. HHSP223014000020B (BPA to HHSP23337073) with the Substance Abuse and Mental Health Services Administration, Contract/Task Order No. 3610X18PO178 with the U.S. Department of Veterans Affairs, and by Alkermes, American Board of Family Medicine, American College of Clinical Pharmacy, American Psychiatric Association, American Psychiatric Nurses Association, American Psychological Association, Association for Behavioral Health and Wellness, Council on Social Work Education, Education Development Center, Janssen Research & Development, National Association of Addiction Treatment Providers, Optum Behavioral Health, Otsuka America Pharmaceutical, PYA, Well Being Trust, and National Academy of Medicine. Any opinions, findings, conclusions, or recommendations expressed in this publication do not necessarily reflect the views of any organization or agency that provided support for the project.
Description based on online resource; title from PDF title page (viewed Oct. 9, 2020).
eBooks on EBSCOhost
Keywords: Mental health services -- United States; Mental health planning -- United States; Mentally ill -- Patients -- United States; Substance abuse -- Patients -- United States; Medical policy -- United States; Mental health services; Mental illness; Drug addiction; Drug abuse; Medical care; Patient-centered health care; Medical policy; Mental Health Services; Mental Disorders; Substance-Related Disorders; Delivery of Health Care; Patient-Centered Care; Health Policy; United States; Patient Care; Services de santé mentale -- États-Unis.; Santé mentale -- Planification -- États-Unis.; Personnes vivant avec un trouble de santé mentale -- Patients -- États-Unis.; Polytoxicomanie -- Patients -- États-Unis.; Politique sanitaire -- États-Unis.; Services de santé mentale; Maladies mentales; Toxicomanie; Prestation de soins; Soins centrés sur le patient; Politique sanitaire; Soins médicaux.; mental disorders; drug abuse; drug addiction; Patient-centered health care; Mental illness; Medical care; Drug addiction; Drug abuse; Medical policy; Mental health planning; Mental health services; Substance abuse -- Patients; United States; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.